If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11x+6=3x-2
We move all terms to the left:
11x+6-(3x-2)=0
We get rid of parentheses
11x-3x+2+6=0
We add all the numbers together, and all the variables
8x+8=0
We move all terms containing x to the left, all other terms to the right
8x=-8
x=-8/8
x=-1
| 5/3=6/x-2 | | 75x+6.25=90+4.75 | | 10x=7-70 | | 1.2/x=4 | | 3x=x+92 | | 4y=y+92 | | 3x=x+49 | | 3x-x+2x+12=3x+9 | | 3(y+2)+y=4(y-1+9 | | 10z=7z-41 | | 60+2s=125 | | 6g+20=2g+20 | | 4y=y+39 | | 6g+12=2g+2” | | 7-2x+7x=8 | | -1-6x=4-8x+3x | | 4b+3(2b+6)=7b+24 | | 40+.25m=25+.35m | | 16+11t=71 | | D=1/2t+3 | | q+13+6=5 | | 5(y+2)+y=3(y-1)=1 | | A=10+(-1a) | | 3.5w=-52.5 | | v/2+10=31 | | 1+7a-4=3+6 | | X-1-3x=5-3x-7 | | -8(5r+5)=-320 | | 5-2.40-1.33=x | | 6x-14=19+x | | 25+8x=12 | | 3/4d=51 |